Parental Perspective on Their Children’s English Learning for Elementary Students through English Drama Performance - Aditya, Ego Agnes; Nur 'Aini, Siti; Senowarsito (Universitas Pendidikan Ganesha, 2024)
Children’s education required support from their learning contexts, both at school and at home. Teachers and principals provided instructions and guidance at school, while parents provided indispensable support to their children’s education. Their perception and insight related to their children’s education were critical to their success. This qualitative study aimed to discover parental perspectives on elementary school children’s English drama performance and how their perspective was paramount to the success of their children’s learning. This study involved 42 parents of elementary school students. Data was collected using a self-report questionnaire and semi-structured interviews. Data was analysed using Interpretive phenomenological analysis (IPA). The results show that three co-related pillars were important to achieve learning objectives: students, teachers, and parents. To support their children, parents needed to respond and perceive how teachers educate their children. Collaboration between teachers and parents was indispensable. The findings suggest parental agreement that English drama performance improved their children’s English skills, despite the complication that came with the activities. In general, parents perceived English drama performance as an essential part of their children’s English skills development. The parental perspective helped English teachers set a better teaching technique to achieve the learning objectives, review, and consider the appropriate learning strategies for the following school year. Children’s education required support from their learning contexts, both at school and at home. Teachers and principals provided instructions and guidance at school, while parents provided indispensable support to their children’s education. Their perception and insight related to their children’s education were critical to their success. This qualitative study aimed to discover parental perspectives on elementary school children’s English drama performance and how their perspective was paramount to the success of their children’s learning. This study involved 42 parents of elementary school students. Data was collected using a self-report questionnaire and semi-structured interviews. Data was analysed using Interpretive phenomenological analysis (IPA). The results show that three co-related pillars were important to achieve learning objectives: students, teachers, and parents. To support their children, parents needed to respond and perceive how teachers educate their children. Collaboration between teachers and parents was indispensable. The findings suggest parental agreement that English drama performance improved their children’s English skills, despite the complication that came with the activities. In general, parents perceived English drama performance as an essential part of their children’s English skills development. The parental perspective helped English teachers set a better teaching technique to achieve the learning objectives, review, and consider the appropriate learning strategies for the following school year.